2022
DOI: 10.3389/fonc.2022.879471
|View full text |Cite
|
Sign up to set email alerts
|

TIM-3 Expression Level on AML Blasts Correlates With Presence of Core Binding Factor Translocations Rather Than Clinical Outcomes

Abstract: BackgroundT-cell immunoglobulin and mucin domain-containing molecule 3 (TIM-3) expresses on leukemic stem and progenitor populations of non-M3 acute myeloid leukemia (AML) as well as T lymphocytes. TIM-3 is thought to be involved in the self-renewal of leukemic stem cells and the immune escape of AML cells, however its correlation with AML prognosis is still controversial and worthy of further investigation.Methodswe simultaneously assessed TIM-3 expression levels of leukemic blasts and T lymphocytes in the bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…The results showed expression of tim-3 was downregulated significantly in AML patients compared to the control group by RT-qPCR analysis. Similar to our results that show the expression of TIM-3 levels in leukemic blasts not significantly correlated with event-free survival (p=0.9873) or the status of remission after chemotherapy induction (p=0.9799) [21].…”
Section: Resultssupporting
confidence: 91%
“…The results showed expression of tim-3 was downregulated significantly in AML patients compared to the control group by RT-qPCR analysis. Similar to our results that show the expression of TIM-3 levels in leukemic blasts not significantly correlated with event-free survival (p=0.9873) or the status of remission after chemotherapy induction (p=0.9799) [21].…”
Section: Resultssupporting
confidence: 91%
“…It has been reported that Tim-3 is not only expressed on immune cells, particularly T cells and NK cells, but is also expressed on leukemic stem cells (LSCs) in AML, which plays a double immunosuppressive role in the anti-tumor response. 34 , 35 In this study, we also detected PD-L1/PD-L2/Gal-9/Tim-3 expression in primary AML cells; however, we had not found the significant difference of ligand expression in AML cells in PB, and there was no significant difference of IC ligand expression between samples from PB and BM, even we know that leukemia bone marrow as tumor microenvironment may play immune suppression which may enhance the IC and ligand expression. In this study, we are unable to evaluate the result, one of the reasons may be due to the limit sample size to make effective comparison, we will continue to collect more AML samples to confirm the result.…”
Section: Discussionmentioning
confidence: 51%